2007
DOI: 10.1002/job.446
|View full text |Cite
|
Sign up to set email alerts
|

Organizational career development is not dead: a case study on managing the new career during organizational change

Abstract: SummaryNew forms of careers have received increased attention in contemporary organizational research. A prominent focus in this research has been whether and how, in an increasingly unpredictable career environment, individuals are taking responsibility for their own career development. The implication is that career is becoming less central to organizational management practices. At the same time there is evidence that organizational changes typically described in this literature (such as delayering the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 39 publications
3
118
0
14
Order By: Relevance
“…Despite this shift toward individual, and not organizational, responsibility and ownership for careers due to the dynamic nature of labor markets, several authors have argued and demonstrated that organizational career management is not dead (e.g., Baruch, 2006;Herriot & Pemberton, 1996;Lips-Wiersma & Hall, 2007;Sturges, Guest, Conway, & Davey, 2002). The transition from predominantly organizational to individualistic career management requires, however, that organizations move away from the traditional command and control, top-down career management and development approach (Baruch, 2006;Lips-Wiersma & Hall, 2007), and become "supportive and developmental" (Baruch, 2006, p. 130) contrast to what some new career theorists have suggested (e.g., Arthur, Inkson, & Pringle, 1999), organizations should not withdraw from active career management but should become differently involved.…”
Section: Introductionmentioning
confidence: 98%
“…Despite this shift toward individual, and not organizational, responsibility and ownership for careers due to the dynamic nature of labor markets, several authors have argued and demonstrated that organizational career management is not dead (e.g., Baruch, 2006;Herriot & Pemberton, 1996;Lips-Wiersma & Hall, 2007;Sturges, Guest, Conway, & Davey, 2002). The transition from predominantly organizational to individualistic career management requires, however, that organizations move away from the traditional command and control, top-down career management and development approach (Baruch, 2006;Lips-Wiersma & Hall, 2007), and become "supportive and developmental" (Baruch, 2006, p. 130) contrast to what some new career theorists have suggested (e.g., Arthur, Inkson, & Pringle, 1999), organizations should not withdraw from active career management but should become differently involved.…”
Section: Introductionmentioning
confidence: 98%
“…There is evidence, however, that the organisational changes typically described in the literature, such as delayering in a quest for flexibility, have had a negative impact on career progress and resulted in resistance to change (Lips-Wiersma & Hall 2007). Organisations focus on career development to build engagement during difficult times so that stressed employees have a positive focus on the future (Knight 2014).…”
Section: Hrm Practices During Pre-mergers and Acquisitionsmentioning
confidence: 99%
“…A well-designed career master plan helps administrators to appropriately perform their responsibilities: first, determine a balance between workers' careers requirements and the organization's manpower requirements (Antoniu, 2010;Ismail, Daud, & Madrah 2011;Lips-Wiersma & Hall, 2007). Second, determine appropriate career instruments in order to help employees to achieve their career goals such as through internal training, formal education, counseling, job rotation, succession plans, work simplification and care the quality of employees' work life in organizations (Chang et al, 2007;Ismail et al, 2011;Koen, Klehe, Van Vianen, Zikic, & Nauta 2010;Kulkarni, 2013).…”
Section: Introductionmentioning
confidence: 99%